Developing an evidence-based prehabilitation programme designed to improve functional outcomes after lumbar fusion surgery - A feasibility study using the Medical Research Council framework. (2nd January 2020) - Lotzke, Hanna; Gutke, Annelie; den Hollander, Marlies; Smeets, Rob; Lundberg, Mari
Abstract: Purpose: A prehabilitation phase is suggested as the ideal way to prepare patients for optimal outcomes from surgery. Our aim was to describe the lessons we learned from developing PREPARE, an evidence-based prehabilitation programme based on a cognitive behavioural approach designed to improve functional outcomes after lumbar fusion surgery. Methods: We used the Medical Research Council (MRC) framework approach for developing and designing a complex intervention, specifically the two phases; 'Development' and 'Feasibility and Piloting'. Various aspects of treatment fidelity were evaluated during the phase 'Feasibility and Piloting'. As part of the feasibility element, a pilot Single Subject Research Design study was performed. Eleven patients awaiting lumbar fusion surgery participated in the study. We evaluated in particular the use and application of outcome measures. Results: Significant lessons were learned which we used to adjust the prehabilitation programme to better fit a surgical context. The original treatment manual was elaborated on, the outcome measures adjusted, and the content of the intervention altered. Finally, the PREPARE programme was published in the form of a study protocol. Conclusions: There are significant lessons to be learned from testing a study protocol before it is implemented in a large-scale randomised controlled trial (RCT).